Perbaikan profil lipid pada perempuan dewasa kelebihan berat badan setelah intervensi sari jeruk kalamansi (Citrus microcarpa) - Surlitah, Sutemy; Setiawan, Budi; Briawan, Dodik (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2017)
The objective of this research was to analyze the effect of calamansi juice intervention on lipid profiles of overweight adult women. The pre-post and randomized single-blinded clinical study were applied on 24 subjects who were randomly and alocated into two group, i.e group A (300 ml 100% pure calamansi juice) and group B (300 ml and 50% concentrante calamansi juice). The juice was given twice a day (each 150 ml) for 28 days and lipid profiles were analyzed before and after intervention. The result showed a significant decrease (p<0.05) after intervention in Triglyseride plasma (TG) level (-23.67±21.81 and -2.33±22.39 mg/dl), low density lipoprotein (LDL-c) -30.58±25.05 and 12.42±26.66 mg/d), total cholesterol (TC) 23.50±30.90 and 12.00±30.80 mg/dl and a significant increase (p<0.05) in high density lipoprotein (HDL-c) plasma level (10.25±11.91 and 0.33±8.57 mg/dl). Meanwhile, in group B there was no significant change in lipid profiles. The intervention of 300 ml pure calamansi juice improved the lipid profile of overweight women.